Madagascar Tourism Sector Review : Unlocking the Tourism Potential of an Unpolished Gem - World Bank (Washington, DC, 2014)
The island nation of Madagascar has a treasure trove of tourism assets, ranging from wildlife viewing to beach tourism to cultural encounters. Yet despite its undeniable tourism potential, its growth has been severely stunted by years of political instability and lack of action on necessary policy reforms and initiatives. While there is much that needs to be done for Madagascar to fulfill its potential in tourism, if adequately addressed, tourism can undoubtedly become a significant contributor to the country's economic revival. This review of the Madagascar tourism sector has been conducted as part of a larger Indian ocean regional tourism integration study. The principal objective of the synthesis is to highlight opportunities to strengthen the countries' tourism sectors through regional integration initiatives. This report is structured as follows: section one gives introduction to the Madagascar study; section two gives overview of the Madagascar tourism sector; section three presents key issues; section four gives recommendations; and section five gives conclusion.